Function and mechanism of long non-coding RNA Gm21284 in the development of hippocampal cholinergic neurons - Cheng, Xiang (Cell Biosci, 2019)
BACKGROUND: Increasing evidence has revealed that long non-coding RNAs (lncRNAs) play a pivotal role in the development of nervous system. Our previous studies have demonstrated that enhanced cholinergic neurogenesis occurs in the subgranular zone (SGZ) of the hippocampal dentate gyrus (DG) after cholinergic denervation, which is closely associated with the core transcription factor Lhx8. This study aimed to identify novel lncRNAs in a denervated hippocampal niche, which may affect cholinergic neurogenesis, and to explore the molecular mechanisms underlying cholinergic neurogenesis. METHODS: The gene expression profiles of the denervated hippocampus were examined by microarray analysis, and targeted lncRNAs were filtered using bioinformatics analysis. The lncRNA Gm21284 was predicted to be associated with Lhx8. RT-PCR and FISH were used to observe the expression and localization of Gm21284 in vitro and in vivo. The interaction between Gm21284 and Lhx8 and miR-30e-3P was verified using the luciferase reporter gene assay. Cell proliferation and differentiation was observed to reveal the effects of Gm21284 in cholinergic neurogenesis. RESULTS: Microarray analysis demonstrated 482 up-regulated and 135 down-regulated mRNAs, 125 up-regulated and 55 down-regulated lncRNAs, and 10 up-regulated and 3 down-regulated miRNAs in the denervated hippocampal niche. Overall, 32 lncRNAs were differentially expressed in the denervated hippocampal niche, which could interact with miR-30e-3p, miR-431, and miR-147. Among these 32 lncRNAs, Gm21284 and Adarb1 were identified after interleaving with lncRNAs in a co-expression network and WGCNA. Gm21284 was mainly located in the hippocampal DG. Furthermore, Gm21284-positive cells were considerably increased in the denervated hippocampus than in the normal side. EdU proliferation assay revealed that the proliferation of neural stem cells was repressed after the overexpression of Gm21284. Compared with the control group, the proportion of ChAT-positive cells increased at 7 days of differentiation of NSCs overexpressing Gm21284. CONCLUSION: Thus, Gm21284 functions as a competing endogenous RNA, which inhibits the proliferation of hippocampal NSCs and promotes their differentiation toward cholinergic neurons by inhibiting miR-30e-3P competitively.